Ultrasensitive Technique for Deep Study in Nonlinear Optical Nanostructures: Z-scan Imaging Technique with Interference Pattern Indicator in Real Time - H. I. Elim (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2024)
To detect a flexible ultrasensitive response’s material particularly with the nonlinear photonics characters, one needs a precise measurement. An excellent experimental setup to study such materials for flexible electro-optics and electronics requires not only the points of important physical parameters, but also the interaction’s mapping. In this communication work, a proposed newly technique of z-scan imaging method is introduced to tackle such high quality achievement. The setup was tested by light-matter interaction observation in as single aggregation of silver (Ag) nanoparticles with the number of nanoparticles in an aggregation target was estimated by 474,552 nanoparticles. According to the first time nonlinear light-matter interaction, an interference pattern was identified in each z position during the measurement of nonlinear absorption coefficient. Such interference pattern was formed due to nonlinear processes. This z scan imaging technique suggest a wide range application to study various flexible photonics materials.